The future of food and agriculture Drivers and triggers for transformation - Bellu, Lorenzo Giovanni (2023)
Lorenzo Giovanni Bellù POLICY SEMINAR The future of food and agriculture – Drivers and triggers for transformation Co-organized by Food and Agriculture Organization (FAO), IFPRI, and the CGIAR Research Initiative on Foresight FEB 1, 2023 - 10:00 TO 11:15AM EST